(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
In this article non-verbal communication is one of the most important areas for the functioning of signs and symbolic information and occupies a significant place in the life of a person and society. In a narrow sense, Kinesics is a doctrine of gestures, primarily hand gestures. In addition, the object of kinesics are mimic gestures, gestures of the head and legs, postures, and symbolic movements.